2006
DOI: 10.1001/archinte.166.20.2191
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Glucose Levels and Incident Diabetes Mellitus in Older Nondiabetic Adults Randomized to Receive 3 Different Classes of Antihypertensive Treatment

Abstract: Fasting glucose levels increase in older adults with hypertension regardless of treatment type. For those taking chlorthalidone vs other medications, the risk of developing FG levels higher than 125 mg/dL (6.9 mmol/L) is modestly greater, but there is no conclusive or consistent evidence that this diuretic-associated increase in DM risk increases the risk of clinical events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(117 citation statements)
references
References 28 publications
6
108
0
1
Order By: Relevance
“…In spite of this unfavorable biochemical finding, the change in fasting glucose levels did not adversely impact CVD outcomes, a finding similar to what we found in the nondiabetic cohort of ALLHAT (15). The possibility has been raised that had ALLHAT been extended to 10 or 15 years of follow-up, the negative effect of elevated fasting glucose levels and the dyslipidemia associated with diuretic use would have become evident (29). The recent report from the 14-year follow-up of the Systolic Hypertension in the Elderly Program (SHEP) does not support this argument (30).…”
Section: Biochemical Changessupporting
confidence: 82%
“…In spite of this unfavorable biochemical finding, the change in fasting glucose levels did not adversely impact CVD outcomes, a finding similar to what we found in the nondiabetic cohort of ALLHAT (15). The possibility has been raised that had ALLHAT been extended to 10 or 15 years of follow-up, the negative effect of elevated fasting glucose levels and the dyslipidemia associated with diuretic use would have become evident (29). The recent report from the 14-year follow-up of the Systolic Hypertension in the Elderly Program (SHEP) does not support this argument (30).…”
Section: Biochemical Changessupporting
confidence: 82%
“…However, they have been linked to IGT, hyperglycemia more than NODM [61][62][63][64][65][66][67][68][69]. Hydrochlorothiazide or chlorthalidone have been reported to cause hyperglycemia more often than other diuretics, and a higher incidence of NODM was reported with chlorthalidone in the ALLHAT trial after 2 and 4 years follow-up [68].…”
Section: Thiazidementioning
confidence: 99%
“…33 No association was seen between diuretic-related changes in FBG or NOD at 2 years and CV or renal disease risk over the subsequent 2.9 years. 35 With 4 additional years of follow-up, the ALLHAT investigators reported that thiazide-related NOD carried a lower risk for CV events than NOD developing in patients receiving either of the other 2 treatments. 36 In the Systolic Hypertension in the Elderly Program (SHEP), 4,732 patients who had been randomized to chlorthalidone or placebo were followed up for a mean of 14.3 years.…”
Section: Thiazide Diuretics and Nodmentioning
confidence: 99%